2016
DOI: 10.1016/j.scijus.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The non-contact detection and identification of blood stained fingerprints using visible wavelength hyperspectral imaging: Part II effectiveness on a range of substrates

Abstract: Biological samples, such as blood, are regularly encountered at violent crime scenes and successful identification is critical for criminal investigations. Blood is one of the most commonly encountered fingerprint contaminants and current identification methods involve presumptive tests or wet chemical enhancement. These are destructive however; can affect subsequent DNA sampling; and do not confirm the presence of blood, meaning they are susceptible to false positives. A novel application of visible wavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The approach carried out by our research group indicated a higher sensitivity and specificity for the detection and identification of blood stains over previously proposed methods [3]. Recent research has since successfully demonstrated the application of this technique for the detection, identification, and visualisation of ridge detail in blood stained fingerprints deposited on white ceramic tiles [19] and a range of other substrates commonly encountered at scenes of crime [20]. To date there has been no comparison between HSI and existing chemical enhancement methods, such as Acid Black.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…The approach carried out by our research group indicated a higher sensitivity and specificity for the detection and identification of blood stains over previously proposed methods [3]. Recent research has since successfully demonstrated the application of this technique for the detection, identification, and visualisation of ridge detail in blood stained fingerprints deposited on white ceramic tiles [19] and a range of other substrates commonly encountered at scenes of crime [20]. To date there has been no comparison between HSI and existing chemical enhancement methods, such as Acid Black.…”
Section: Introductionmentioning
confidence: 79%
“…The HSI system used in this study was the same setup detailed in [3] and [19,20], consisting of a liquid crystal tuneable filter (LCTF) coupled to a 2.3 megapixel Point Grey camera and a light source for scene illumination. The light source was comprised of two 40W LEDs; one violet giving an output at 410nm and one white giving an output between 450 and 700 nm.…”
Section: The Hyperspectral Imaging (Hsi) Systemmentioning
confidence: 99%
See 3 more Smart Citations